Synthesis of Hematite Nano Material and Its Effect on Properties of Water Based Drilling Mud - Ahmed, Narjis M.; Abdul Hussein, Hassan A.; Flayyih, Mustafa H. (Journal of Petroleum Research and Studies, 2021)
The worldwide use of nanotechnology in most industries, such as in oil and gas industries, the world now has been directed towards introducing this modern technology in drilling fluids for the purpose of reaching and extracting hydrocarbons that exist at high depth where high temperatures and high pressure present using this technology to achieve the required mud properties with lowest cost. In this research, the particles of Nano hematite were prepared in laboratory using two methods, the first method by chemical reaction between iron nitrate (Fe (NO3)3• 9H2O) and ammonium hydroxide (NH4OH), after that, prepared Nano-materials were subjected to AFM, XRD testing in order to investigate the size and type of particles, the investigations showed that the formed particles were Fe2O3 (<100nm). The second method is similar to the first method except adding (CTAB) material in order to reduce the interfacial tension leading to 4.5nm Nano-material. Three samples of drilling mud were prepared, the first sample was prepared from water and bentonite only, the second sample was prepared from water, bentonite and nano (prepared from first method), the third samples was prepared from water, bentonite and nano (prepared from second method), rheological properties, filtration, density, lubricity, sagging and magnetism properties were measured by analyzing and comparing the results. The results were obtained showed that the small effect of nano material filtration, density, lubricity, and sagging properties, except the viscosity increase when the second sample of Nano hematite was added to the mud prepared from water and bentonite. Also, the magnetism increase when the second sample of nano hematite was added to the mud prepared from water and bentonite, due to the difference in the molecular arrangement caused by the presence of CTAB.